1999
DOI: 10.1677/joe.0.1600049
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific response of IGF-I mRNA expression to obesity-associated GH decline in the male Zucker fatty rat

Abstract: Diminished GH secretion is a well known association of obesity. As in obese humans, Zucker fatty rats develop a progressive GH deficiency, present at 6 weeks of age and maximal at 10 to 12 weeks. The aim of this study was to investigate the GH dependence of IGF-I gene expression in liver and extrahepatic tissues of the obese Zucker rat as a model of progressive GH reduction during adult life. Six-and 11-week-old obese Zucker rats and their lean littermates were used to compare body weight, glycemia, insulinemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
5
2
Order By: Relevance
“…1012 The diminished growth hormone secretion may be accompanied with overtly elevated levels of reactive oxygen species (ROS) and reduced lean body mass in obesity. 2, 9, 10, 13 Thus the present study was undertaken to examine the impact of overexpression of IGF-1, an essential cardiac survival factor, 14 on high fat diet-induced cardiac geometric, morphological and functional defects. In an effort to elucidate the cellular mechanisms underscoring IGF-1- and high fat diet-induced myocardial alterations, if any, special attention was paid to insulin signaling, apoptosis, mitochondrial integrity including ATP content, cytochrome C release, peroxisome proliferator-activated receptor γ (PPARγ) coactivator 1α (PGC1α) and uncoupling protein 2 (UCP-2).…”
Section: Introductionmentioning
confidence: 99%
“…1012 The diminished growth hormone secretion may be accompanied with overtly elevated levels of reactive oxygen species (ROS) and reduced lean body mass in obesity. 2, 9, 10, 13 Thus the present study was undertaken to examine the impact of overexpression of IGF-1, an essential cardiac survival factor, 14 on high fat diet-induced cardiac geometric, morphological and functional defects. In an effort to elucidate the cellular mechanisms underscoring IGF-1- and high fat diet-induced myocardial alterations, if any, special attention was paid to insulin signaling, apoptosis, mitochondrial integrity including ATP content, cytochrome C release, peroxisome proliferator-activated receptor γ (PPARγ) coactivator 1α (PGC1α) and uncoupling protein 2 (UCP-2).…”
Section: Introductionmentioning
confidence: 99%
“…Our results obtained in PCH were, surprisingly, not consistent with those reported previously by Melián et al [23]who observed a decreased IGF-1 mRNA expression in liver and other tissues in the male Zucker fatty rat. We, therefore, decided to investigate freshly isolated hepatocytes and whole-liver tissue from obese and lean Zucker rats.…”
Section: Resultscontrasting
confidence: 99%
“…Our results using hepatocytes in culture contrast with those of Melián et al [23]who used a ribonuclease protection assay to study whole-liver tissue mRNA. These investigators reported decreased IGF-I and IGF-IB mRNA levels in 6- and 11-week-old fa/fa rats as compared with lean controls.…”
Section: Discussioncontrasting
confidence: 99%
“…The factors which may regulate diminished Akt activation during hyperglycemia will require further experimentation. Similarly, it is also possible that reduced availability of circulating growth factors, decreased expression of local growth factors or alterations in cytokine levels may also play a role regulating Akt signaling 31. This latter possibility is an intriguing alternative that we are actively pursuing.…”
Section: Discussionmentioning
confidence: 99%